Sarcopenia and mortality in older people living in a nursing home in Turkey. Issue 7 (20th July 2016) - Yalcin, Ahmet; Aras, Sevgi; Atmis, Volkan; Cengiz, Ozlem Karaarslan; Cinar, Esat; Atli, Teslime; Varli, Murat
Abstract : Aim: The aim of the present study was to evaluate the relationship between mortality and sarcopenia defined by the criteria of the European Working Group on Sarcopenia in Older People in older nursing home residents in Turkey. Methods: This was an observational prospective study. Nursing home residents who were aged older than 65 years and living in the Seyranbagları Nursing Home and Rehabilitation Center (Ankara, Turkey) were recruited for the study. The main outcome measure was the relationship between sarcopenia and mortality. Diagnosis of sarcopenia was carried out according to the European Working Group on Sarcopenia in Older People criteria. Bioelectrical impedance analysis was used for skeletal muscle mass measurement. Muscle strength and muscle performance were evaluated by handgrip testing and gait speed, respectively. Mortality was assessed at the end of 2 years. The Kaplan–Meier method and Cox regression analysis were used to evaluate the relationship between sarcopenia and all‐cause mortality. Results: The prevalence of sarcopenia and severe sarcopenia were 29% and 25.4%, respectively. A total of 44% (18) of sarcopenic participants died, whereas 15% (15) of participants without sarcopenia died after 2 years of follow up ( P  < 0.001). After adjusting for confounding factors, sarcopenia was associated with all‐cause mortality among older nursing home residents in Turkey (HR 2.38, 95% CI 1.04–5.46; P  = 0.039). However, sarcopenia was not significantly related with mortality after adjustment of MNA score (HR 2.04, 95% CI 0.85–4.9; P  = 0.1). Conclusions: Sarcopenia independently increases all‐cause mortality in older nursing home residents in Turkey. Nutritional status plays a role in sarcopenia‐related mortality.Geriatr Gerontol Int 2017; 17: 1118–1124 .